2017
DOI: 10.1371/journal.pone.0175498
|View full text |Cite
|
Sign up to set email alerts
|

Effects and underlying mechanisms of irisin on the proliferation and apoptosis of pancreatic β cells

Abstract: Pancreatic β cell dysfunction and reduction due to glucose toxicity play a crucial role in the development of type 2 diabetes mellitus (T2DM). Irisin, a novel exercise-induced myokine, reduces obesity, improves insulin resistance and lowers blood glucose by promoting the browning of white adipose tissue, thereby enhancing thermogenesis and increasing energy expenditure. Recent studies have reported that irisin promotes cell proliferation and protects cells from apoptosis. However, the effects of irisin on panc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
72
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(80 citation statements)
references
References 13 publications
5
72
0
3
Order By: Relevance
“…In previous studies, appropriate increase in circulating irisin can rescue insulin sensitivity of C57BL/6 mice with diet‐induced insulin resistance (Lopez‐Legarrea et al, ). Similarly, irisin can cause the reduced apoptosis of INS‐1 cells induced by high glucose and the increased secretion of insulin (Liu et al, ). In the present study, the significantly decreased irisin was also detected during the exposure to high‐glucose environment, while restored by metformin.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, appropriate increase in circulating irisin can rescue insulin sensitivity of C57BL/6 mice with diet‐induced insulin resistance (Lopez‐Legarrea et al, ). Similarly, irisin can cause the reduced apoptosis of INS‐1 cells induced by high glucose and the increased secretion of insulin (Liu et al, ). In the present study, the significantly decreased irisin was also detected during the exposure to high‐glucose environment, while restored by metformin.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that, as of today, there is no evidence that circulating irisin may affect body weight in nondiabetic mice. Moreover, the results on the ability of irisin to reduce body weight and food intake in diabetic mice or rats have been conflicting . Indeed, it is possible that the effects of irisin administration on food intake may be dependent upon the timing and/or route of administration.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the results on the ability of irisin to reduce body weight and food intake in diabetic mice or rats have been conflicting. [17][18][19][20][21][22][23][24][25]31 Indeed, it is possible that the effects of irisin administration on food intake may be dependent upon the timing and/or route of administration. The reported irisin-induced increase in food intake (but not in body weight) in nonobese, nondiabetic rats occurred following intracerebroventricular infusion of the hormone for 7 days and was associated with increased circulating ghrelin and decreased serum leptin and POMC mRNA levels in the hypothalamus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the regulatory actions on β cells, it has been reported that irisin administration attenuates β-cell apoptosis and restores β-cell function under glucotoxic condition [22]. In addition, a recent study has shown that irisin suppresses apoptosis in β cells and islets under lipotoxic condition via modulation of protein kinase B/B-cell lymphoma 2 (BCL2) signaling pathway [23].…”
Section: Introductionmentioning
confidence: 99%